Growth and Betacyanin Content of Beetroots (Beta vulgaris L.) Under Water Deficit in A Tropical Condition - S.M. Sitompul; Mochammad Roviq; Ervina Riedo (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The present study, a part of a series of studies carried out to explore the possibility of beetroot cultivation in the tropics on highlands, was designed to investigate the growth and betacyanin content of beetroot plants in response to water deficit in a tropical condition. The water deficit was executed through varied watering intervals consisting of once three (as control), four, five, six and seven days. A randomized block design with five replicates was used to impose the treatments. The effect of water deficit was found to reduce the leaf water content, the biomass production (total dry weight) and the root yields of beetroot plants. Root dry weight decreased by more than 20% and 50% with the watering interval once four and seven days respectively compared with that once three days. The betacyanin content of roots was not influenced by the water deficit when expressed per unit volume of fresh root extracts (340.5 ± 60.1 mg/l), and increased when expressed per unit root dry weight. It is suggested that an optimal supply of water, for instance watering once three days, is necessary to obtain beetroot plants growing optimally and producing a high root yield and betacyanin content of roots.